The role of prooxidative and antioxidant processes in periodontal tissue in the mechanisms of formation of adrenalin damage of myocardium and experimental periodontitis and their correction with Corvitin - Oleh Horodetskyy (Kazimierz Wielki University, 2019)
The aim of our study was to determine the antioxidant activity and prooxidative processes in the formation mechanisms in periodontal adrenalin myocardial damage and experimental periodontitis and their correction with corvitin. For this purpose, we conducted a study on 54 nonlinear white male rats, which were divided into six groups. First - control, second, third, fourth and fifth - a group of animals with adrenaline injury of myocarditis during the course of experimental periodontitis before correction of corvitin to according to the 1st, 7th, 10th and 17th days of the experiment and the sixth group - animals with adrenaline injury of myocarditis during the course of experimental periodontitis after adjustment corvitin. The results showed that when combined pathology antioxidant activity of prooxidative processes going towards depression of antioxidant protection against the growing LPO. After entering corvitin - reduced rates of LPO and increases the activity of enzymes AOC, that indicating the antioxidant and cardioprotective properties of the drug.